System Quality dan Information Quality terhadap Kinerja Pegawai melalui User Satisfaction menggunakan SIPD di Dinas Ketahanan Pangan dan Pertanian Kota Madiun - Kusuma, Firdaus Miftakh; Ardianto, Yusaq Tomo; Prasetya, Dwi Arman (Jurnal Teknologi dan Manajemen Informatika, 2022)
The Regional Government Information System (SIPD in Bahasa) is a management information system that is used to administer, document, and process regional development data into information. It serves to make decisions, and policies and build a unified database. The data is integrated from district/city, provincial and national levels. This study uses path analysis with a total sample of 43 employees. In the research, the coefficient value of the System Quality variable on User Satisfaction has a direct effect of 0.414. The Information Quality variable on User Satisfaction has a direct effect of 0.352. The System Quality variable on Employee Performance has a direct influence of 0.229. The variable Information Quality on Employee Performance has a direct effect of 0.449. Furthermore, the influence of System Quality on Employee Performance through User Satisfaction has an indirect effect of 0.186 with a total amount of 0.415. The influence of Information Quality on Employee Performance through User Satisfaction has an indirect effect of 0.158 with a total amount of 0.610.